Concentrations of methane in sediment core GeoB24376-1 from the Calabrian accretionary wedge, RV Sonne cruise SO278 - Pape, Thomas; Malnati, Janice; Tseng, Yiting; Bohrmann, Gerhard (PANGAEA, 2023)
Shallow sediment cores were collected with a gravity corer and a multi corer from several sites at the Sartori Mud Volcano in the Calabrian accretionary prism during cruise SO278 with R/V SONNE. In order to determine ex-situ concentrations and stable C and H isotopic compositions of methane dissolved in pore water, sediment samples were taken from the sediment cores with cut-off syringes and transferred into glass vials. Methane concentrations in the headspace gas were determined by use of gas chromatography (GC) and used to calculate concentrations of methane dissolved in pore water (uncorrected for sediment porosity and Bunsen coefficient). Stable C and H isotopic compositions of methane were determined by use of GC-isotope ratio mass spectrometry.
Keywords: Calabrian accretionary prism; Headspace Gas; Ionian Sea; Mediterranean Ridge accretionary complex; Methane concentration; pore water dissolved methane; R/V SONNE; Sartori mud volcano; SO278; stable carbon isotope; stable hydrogen isotope (0)